Therapeutic approach to acute otitis media in primary care in an urban area. Delayed antibiotic prescription evaluation - María García Ventura; César García Vera; Juan Ruiz-Canela Cáceres (Elsevier, 2022)
Background and objectives: Acute otitis media (AOM) is one of the most frequent causes of consultation and antibiotic prescription in pediatrics. The objective of this work is to evaluate the practice of delayed antibiotic prescription in AOM in pediatrics in primary care. Material and methods: Observational, retrospective study, through reviewing of medical records in a Primary Care Center of Aragon Community of children with OMA in which doctors perform delayed prescription. Logistic regression analyzes possibly related to antibiotic prescription factors. Results: 1390 episodes of AOM are analyzed in 696 patients. Immediate antibiotic prescription is performed in 67.6% (95% CI: 65.1-70.0%) of episodes, exclusive symptomatic in 13.7% (IC 95: 11.9-15.6%), and delayed antibiotic in 18.7% (IC 95: 16.7%-20.8%), finally being given in 53.5% (IC 95: 47.4-59.5%) of these. Factors significantly related to final antimicrobial dispensation in delayed prescription are aged between 0 and 2 years (OR 1.89, 95% CI: 1.25-2.87), bilaterality (OR 2.54, 95% CI: 1.48-4.35), ear pain (OR 0.49, CI 95: 0.29-0.82), fever (OR 2.67, IC 95: 1.95-3.65), bulging (OR 3,63; IC 95: 2,50-5,29) and otorrhea (OR 25.98; IC 95: 12.75-52.92). The same factors have influence on global prescription of antibiotics. Amoxicillin (74.6%) is the most indicated antibiotic, followed by Amoxicillin-Clavulanic (17.0%). Conclusions: Delayed prescription in AOM seems to be useful to reduce antibiotics consumption, being necessary to advance in its implantation. Resume: Introducción: La otitis media aguda (OMA) es una de las causas más frecuentes de consulta y prescripción antibiótica en pediatría. Es objetivo de este trabajo valorar la prescripción antibiótica diferida en OMA en pediatría en atención primaria. Material y métodos: Estudio observacional, retrospectivo, mediante revisión de historias clínicas en un Centro de Salud urbano de la Comunidad Autónoma de Aragón de niños con OMA de tres cupos en los que los facultativos realizan prescripción diferida. Mediante regresión logística se analizan las variables posiblemente relacionadas con la prescripción antibiótica. Resultados: Se analizan 1390 episodios de OMA en 696 pacientes. Se realizó prescripción inmediata de antibióticos en el 67,6% (IC 95: 65,1-70,0%) de episodios, sintomática exclusiva en el 13,7% (IC 95: 11,9-15,6%), y antibiótica diferida en el 18,7% (IC 95: 16,7%-20,8%), dispensándose finalmente el antimicrobiano en el 53,5% (IC 95: 47,4-59,5%) de estos últimos. Factores relacionados significativamente con la adquisición final antimicrobiana en prescripción diferida son la edad entre 0−2 años (OR 1,89; IC 95: 1,25-2,87), la bilateralidad (OR 2,54; IC 95: 1,48-4,35), la otalgia (OR 0,49; IC 95: 0,29-0,82), la fiebre (OR 2,67; IC 95: 1,95-3,65), el abombamiento (OR 3,63; IC 95: 2,50-5,29) y la otorrea (OR 25,98; IC 95: 12,75-52,92). Los mismos factores influyen en la prescripción global de antibióticos. Se indicó principalmente Amoxicilina (74,6%), seguido de Amoxicilina-Clavulánico (17,0%). Conclusiones: La prescripción diferida en OMA parece útil para disminuir el consumo de antibióticos, siendo necesario avanzar en su implantación.